2021
DOI: 10.1364/ol.431933
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN-based deep ultraviolet micro-LED emitting at 275 nm

Abstract: The investigation of electrical and optical properties of micro-scale AlGaN deep ultraviolet (DUV) light-emitting diodes (LEDs) emitting at ∼ 275 n m was carried out, with an emphasis on fabricated devices having a diameter of 300, 200, 100, 50, and 20 µm, respectively. It was revealed that the LED chips with smaller mesa areas deliver considerably higher light output power density; meanwhile, they can sustain a higher current density, which is mainly attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 31 publications
2
61
0
Order By: Relevance
“…To date, AlGaN-based deep-ultraviolet (DUV) LEDs have exhibited relatively low external quantum efficiencies (EQEs) because of the properties intrinsic to aluminum-rich group III-nitride materials. In contrast, AlGaN-based ultraviolet-B (UVB) LEDs began attracting great attention after the implementation of the Minamata Convention on Mercury. There is much potential for such LEDs to be used in medical and agricultural applications, including cancer immunotherapy; treatment of psoriasis, vitiligo, and pemphigus vulgaris; plant growth under UVB lighting; and the production of phytochemicals in the green leaves of vegetables. Verhaeghe et al found that narrow-band (NB-UVB) emission therapy at 310 nm was more effective than broad-band (BB-UVB) therapy at 280–320 nm in the treatment of psoriasis and atopic dermatitis; furthermore, NB-UVB phototherapy at 310 nm emission appears suitable for cancer therapy and skin cure therapy. Several reports have disclosed high EQEs (2–5%) when combining low-dislocation-density AlN template substrates, an optimized Si-doped n-AlGaN buffer layer, an electron injection layer, a transparent p-AlGaN layer, and reflective electrodes. Although AlGaN-based UVB LEDs have uses industrially, a few issues remain to be resolved for the development of AlGaN-based NB-UVB LEDs in addition to low EQEs, including low wall plug efficiencies (WPEs) and short aging lifetimes. In medical and agricultural settings, a narrower full-width at half-maximum (FWHM) of the emitted light would be preferred for higher absorption efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…To date, AlGaN-based deep-ultraviolet (DUV) LEDs have exhibited relatively low external quantum efficiencies (EQEs) because of the properties intrinsic to aluminum-rich group III-nitride materials. In contrast, AlGaN-based ultraviolet-B (UVB) LEDs began attracting great attention after the implementation of the Minamata Convention on Mercury. There is much potential for such LEDs to be used in medical and agricultural applications, including cancer immunotherapy; treatment of psoriasis, vitiligo, and pemphigus vulgaris; plant growth under UVB lighting; and the production of phytochemicals in the green leaves of vegetables. Verhaeghe et al found that narrow-band (NB-UVB) emission therapy at 310 nm was more effective than broad-band (BB-UVB) therapy at 280–320 nm in the treatment of psoriasis and atopic dermatitis; furthermore, NB-UVB phototherapy at 310 nm emission appears suitable for cancer therapy and skin cure therapy. Several reports have disclosed high EQEs (2–5%) when combining low-dislocation-density AlN template substrates, an optimized Si-doped n-AlGaN buffer layer, an electron injection layer, a transparent p-AlGaN layer, and reflective electrodes. Although AlGaN-based UVB LEDs have uses industrially, a few issues remain to be resolved for the development of AlGaN-based NB-UVB LEDs in addition to low EQEs, including low wall plug efficiencies (WPEs) and short aging lifetimes. In medical and agricultural settings, a narrower full-width at half-maximum (FWHM) of the emitted light would be preferred for higher absorption efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are numerous sensing and optical communication applications as well, importantly, the UVC has been verified as one of effective ways to kill COVID-19. [1,3,7,[26][27][28][29][30][31]…”
Section: Classifications and Applicationsmentioning
confidence: 99%
“…UV LEDs and their applications with different wavebands. [1,3,7,[22][23][24][25][26][27][28][29][30][31] (λ)), hv is the photon energy and q is the elementary charge. P out refers to the light output power (LOP) of the UV LED, P in represents the applied electrical power, which is the product of the applied current (I) and voltage (V) numerically, and EE is ratio of useful output power to the total input power.…”
Section: Iqementioning
confidence: 99%
“…Environment-friendly AlGaN-based UVB LEDs with monochromatic light emission are inevitable for both medical and agricultural applications 1 – 9 . The selection of green AlGaN material has many other promising features, such as high internal-quantum-efficiency (IQE) from the multi-quantum-well (MQWs) as well as reasonable level of optical and electrical properties 4 , 8 , 11 , 14 , 15 . The AlGaN-based semiconductors assist in substantial reduction of UV LED and LD production cost, partially due to their ability to be monolithically grown on low-cost c-sapphire substrates in low-pressure metal–organic vapour phase epitaxy (LP-MOVPE) reactors 4 , 8 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%